2000
DOI: 10.1080/713654959
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal digesta viscosity decreases during coccidial infection in broilers

Abstract: 1. The effect of intestinal digesta viscosity on bird performance in chickens with coccidiosis was compared to those without coccidiosis. 2. Six hundred chicks were divided into five groups: one control group was fed a basal maize/soyabean-based diet and the other groups were fed the basal diet supplemented with 2, 4, 6 or 8 g carboxymethyl cellulose (CMC) per kg of feed. At 14 d of age half the birds were individually inoculated with sporulated oocysts of Eimeria acervulina and Eimeria praecox. 3. Intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Waldenstedt et al (2000) already showed that coccidial infection decreases intestinal digesta viscosity. It is unclear whether the reduction in viscosity observed in the present study was to be attributed solely to the coccidia or whether C. perfringens also played a role.…”
Section: Discussionmentioning
confidence: 93%
“…Waldenstedt et al (2000) already showed that coccidial infection decreases intestinal digesta viscosity. It is unclear whether the reduction in viscosity observed in the present study was to be attributed solely to the coccidia or whether C. perfringens also played a role.…”
Section: Discussionmentioning
confidence: 93%
“…Viscosity and fermentability of fibre interacted to modify digesta viscosity. Dietary CMC caused high digesta viscosity in swine (30) and poultry (31) , which was related to the high solubility of CMC (27) . The high in vivo viscosity matched perfectly with the high in vitro viscosity, and thus appeared to confirm the paradigm that a high-viscosity diet results in high digesta viscosity (2) .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, digestion may be further reduced with feeds producing highly viscous digesta, with Waldenstedt et al (2000) suggesting that these feeds may increase digestive and health problems thereby decreasing the availability of nutrients.…”
Section: Introductionmentioning
confidence: 97%